2018
DOI: 10.1104/pp.18.01408
|View full text |Cite
|
Sign up to set email alerts
|

A Methyltransferase Trio Essential for Phosphatidylcholine Biosynthesis and Growth

Abstract: Phosphatidylcholine (PC) is a primary class of membrane lipids in most eukaryotes. In plants, the primary PC biosynthetic pathway and its role in plant growth and development remain elusive due to lack of a mutant model with substantially decreased PC content. Recently, a double mutant of Arabidopsis (Arabidopsis thaliana) PHOSPHO-BASE N-METHYLTRANSFERASE 1 (PMT1) and PMT3 was reported with reduced PC content and defective plant growth. However, residual PC content as well as the nonlethal phenotype of the mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…DAG is readily converted by DAG kinase to produce PA, a representative lipid second messenger in plants, but the involvement of a specific diacylglycerol kinase (DGK) or PA signal in root growth remains unclear. However, PCho is known to be involved in root growth because knock‐out of PMT1, a primary enzyme that produces PCho from PEtn conferred reduced PCho level and root length, which were rescued by exogenous PCho supplementation (Cruz‐Ramírez et al ., ; Liu et al ., ). Thus, we tested whether the reduced root growth in the knock‐down mutant lines was rescued by exogenous PCho supplementation.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…DAG is readily converted by DAG kinase to produce PA, a representative lipid second messenger in plants, but the involvement of a specific diacylglycerol kinase (DGK) or PA signal in root growth remains unclear. However, PCho is known to be involved in root growth because knock‐out of PMT1, a primary enzyme that produces PCho from PEtn conferred reduced PCho level and root length, which were rescued by exogenous PCho supplementation (Cruz‐Ramírez et al ., ; Liu et al ., ). Thus, we tested whether the reduced root growth in the knock‐down mutant lines was rescued by exogenous PCho supplementation.…”
Section: Resultsmentioning
confidence: 97%
“…Previous reports showed that mutation in PMT1 but not PMT2 or PMT3 affected root growth (Cruz‐Ramírez et al ., ; Lee and Jez, ; Liu et al ., ), and additional mutation in PMT2 further shortens the root length of pmt1 mutant (Liu et al ., ). PCho supplementation to these mutants ( pmt1 and pmt1 pmt2 ) rescued the root length but did not affect the wild type (Liu et al ., ). The short root phenotype in our knock‐down mutant lines of NPC2 and NPC6 was also rescued by PCho; hence NPC2 and NPC6 may function in roots to hydrolyze PC to produce PCho for their growth.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations